2012
DOI: 10.1177/0098628312456615
|View full text |Cite
|
Sign up to set email alerts
|

Participants at Your Fingertips

Abstract: The literature suggests students gain important skills when directly involved with faculty in research. However, students at smaller institutions are often faced with limited research opportunities and faculty members are faced with limited participant-pools, funding, and space to perform research. Amazon's Mechanical Turk (MTurk) may provide a solution to many of these problems. MTurk provides an online human participant-pool, along with tools to build experiments, and it allows data to be collected quickly a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 103 publications
(39 citation statements)
references
References 17 publications
0
39
0
Order By: Relevance
“…These individuals were unselected except that they were required to live in the United States and to have had their work approved (vs. rejected) in 95% of the jobs (HITs) they completed previously on MTurk. A high percentage of approved HITs indicates that the participant, in the judgement of other researchers, has reliably completed jobs in the past (Johnson & Borden, 2012). With these requirements, research has shown that MTurk data is comparable to that collected in the laboratory (Johnson & Borden, 2012).…”
Section: Methods Participantsmentioning
confidence: 99%
“…These individuals were unselected except that they were required to live in the United States and to have had their work approved (vs. rejected) in 95% of the jobs (HITs) they completed previously on MTurk. A high percentage of approved HITs indicates that the participant, in the judgement of other researchers, has reliably completed jobs in the past (Johnson & Borden, 2012). With these requirements, research has shown that MTurk data is comparable to that collected in the laboratory (Johnson & Borden, 2012).…”
Section: Methods Participantsmentioning
confidence: 99%
“…Through an online platform called Amazon's Mechanical Turk, 115 participants volunteered to complete the study and were compensated $1.50 (Men = 38; age, M = 34.22 years, SD = 11.55 years; 85% White; full narrative, n = 38, condensed narrative, n = 38, non-narrative condition, n = 39). The sample consisted of participants from 30 states, 10 religious affiliations (one reporting Islam), and 63% were employed full or part time, 12% student, 4% retired, and 21% other (see Buhrmester, Kwang, &Gosling, 2011 andJohnson &Borden, 2012 for validity of MTurk data).…”
Section: Methodsmentioning
confidence: 99%
“…MTurk is an online platform in which adults register to complete various tasks, such as proofreading, indexing, and research surveys. Research data collected through MTurk and other on-line sites are comparable in quality to those gathered using other recruitment and survey methods (Buhrmester, Kwang, & Gosling, 2011;Johnson & Borden, 2012). All survey completers received $2 for their participation.…”
Section: Sample and Participant Selectionmentioning
confidence: 99%